Selective Inhibition of PAR4 (Protease-Activated Receptor 4)-Mediated Platelet Activation by a Synthetic Nonanticoagulant Heparin Analog - Lin, Yu-Chuan; Ko, Yen-Chun; Hung, Shang-Cheng; Lin, Ying-Ting; Lee, Jia-Hau; Tsai, Ju-Ying; Kung, Po-Hsiung; Tsai, Meng-Chun; Chen, Yih-Fung; Wu, Chin-Chung (Arteriosclerosis, thrombosis, and vascular biology, 2019)
OBJECTIVE—PAR4 (protease-activated receptor 4), one of the thrombin receptors in human platelets, has emerged as a promising target for the treatment of arterial thrombotic disease. Previous studies implied that thrombin exosite II, known as a binding site for heparin, may be involved in thrombin-induced PAR4 activation. In the present study, a heparin octasaccharide analog containing the thrombin exosite II–binding domain of heparin was chemically synthesized and investigated for anti-PAR4 effect. APPROACH AND RESULTS—PAR4-mediated platelet aggregation was examined using either thrombin in the presence of a PAR1 antagonist or γ-thrombin, which selectively activates PAR4. SCH-28 specifically inhibits PAR4-mediated platelet aggregation, as well as the signaling events downstream of PAR4 in response to thrombin. Moreover, SCH-28 prevents thrombin-induced β-arrestin recruitment to PAR4 but not PAR1 in Chinese Hamster Ovary-K1 cells using a commercial enzymatic complementation assay. Compared with heparin, SCH-28 is more potent in inhibiting PAR4-mediated platelet aggregation but has no significant anticoagulant activity. In an in vitro thrombosis model, SCH-28 reduces thrombus formation under whole blood arterial flow conditions. CONCLUSIONS—SCH-28, a synthetic small-molecular and nonanticoagulant heparin analog, inhibits thrombin-induced PAR4 activation by interfering with thrombin exosite II, a mechanism of action distinct from other PAR4 inhibitors that target the receptor. The characteristics of SCH-28 provide a new strategy for targeting PAR4 with the potential for the treatment of arterial thrombosis.